2017
DOI: 10.1126/science.aaf9398
|View full text |Cite
|
Sign up to set email alerts
|

Strong peak in T c of Sr 2 RuO 4 under uniaxial pressure

Abstract: Sr & RuO ' is an unconventional superconductor that has attracted widespread study because of its high purity and the possibility that its superconducting order parameter has odd parity. We study the dependence of its superconductivity on anisotropic strain. Applying uniaxial pressures of up to ~1 GPa along a 〈100〉 direction ( -axis) of the crystal lattice results in . increasing from 1.5 K in the unstrained material to 3.4 K at compression by ≈0.6%, and then falling steeply. Calculations give evidence that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
261
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(285 citation statements)
references
References 83 publications
21
261
2
1
Order By: Relevance
“…It should also be mentioned that a superconducting state can exist with an enhanced transition temperature, the so-called 3-K phase. This is observed in eutectic crystals [28][29][30] or in bulk crystals under uniaxial strain [31][32][33].Fluxoid quantization can be investigated by measuring magnetoresistance oscillations as a function of a field applied along the axis of the ring in the regime of the resistive transition, known as the Little-Parks (LP) oscillations [34]. The LP oscillations originate from the oscillations in the free energy and hence in the transition temperature T c , caused by field-induced supercurrents that flow to satisfy the quantization condition.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…It should also be mentioned that a superconducting state can exist with an enhanced transition temperature, the so-called 3-K phase. This is observed in eutectic crystals [28][29][30] or in bulk crystals under uniaxial strain [31][32][33].Fluxoid quantization can be investigated by measuring magnetoresistance oscillations as a function of a field applied along the axis of the ring in the regime of the resistive transition, known as the Little-Parks (LP) oscillations [34]. The LP oscillations originate from the oscillations in the free energy and hence in the transition temperature T c , caused by field-induced supercurrents that flow to satisfy the quantization condition.…”
mentioning
confidence: 85%
“…1(b). There are indications that the order parameter in the 3-K phase is not ESP [33,35]. However, the LP oscillations are robust, regardless of the pairing symmetry or the number of components of the order parameter.…”
mentioning
confidence: 99%
“…In the case of CaRuO 3 , only recently have films with very low residual resistivities helped to reveal a Fermi liquid ground state below 1.5 K, where previous studies suggested non-Fermi liquid behavior. 7 Moreover, the properties of ruthenates are known to respond dramatically to dimensionality, [8][9][10] strain, [11][12][13] and pressure, 14,15 making them an ideal system for exploring the effects of biaxial strain and dimensional confinement in epitaxial thin films. Therefore, the ability to synthesize ruthenate thin films with extremely low amounts of disorder will be crucial for understanding how their emergent properties and ground states can be manipulated and controlled in thin film form.…”
mentioning
confidence: 99%
“…The latter derives from the d xy orbital mainly, with the electronlike Fermi surface slightly below the van Hove points [k = (π/a, 0) and (0, π/a)] with a lattice constant a which we will set equal to 1 in the following. Thus the Fermi surface structure is affected by the physical and/or chemical tunings, such as surface distortion, La doping and strain effects [15][16][17][18][19][20][21][22][23]. These modifications may lead to a Lifshitz transition in the γ band near the van Hove points, which is closely connected with the topological property characterized by the Chern number [24].…”
Section: Introductionmentioning
confidence: 99%